Not so solitary? White rhinos seek company when relaxed - Vera Pfannerstill; Onkgopotse Somalia Maboga (Pachyderm)
White rhinoceros (Ceratotherium simum simum) have been classified as “semi-social” as they often form groups or temporary aggregations of two to six individuals (Owen-Smith 1975; Patton et al. 2016; Pienaar 1994; Shrader and Owen-Smith 2002). Social behaviours such as grazing, and/or walking together and lying side by side, rubbing their head and body (sides) on another rhino and making panting contact calls, have been described in other studies (Owen-Smith 1975; Jenikejew et al. 2020). Playful behaviour such as horn wrestling has also been observed before in white rhinos (Owen-Smith 1975; Cinková and Bičík 2013).